From Uber Eats to Cornershop: The repositioning of Uber in the Brazilian Market - Dias Barbosa, Sophia (2023)
The arrival, development and closure in Brazil of the activities of Uber Eats, Uber Technologies Inc.'s online food delivery service, are analyzed in this teaching case. Over five years in the country, while the company operated under intense competition, the platform also had to deal with the social movement for labor rights of the deliverers and the consequent political and legal decisions that affected the company-worker relationship.  The case assesses the strategic-operational challenges of repositioning the brand, now more segmented in the supermarket delivery sector,  after the acquisition of Cornershop.